Climate change mitigation potential of cascading utilization of wood resources - Jang, Eun-Kyung; Kim, Min-Ji; Yoon, Sae-Min; Eom, Chang-Deuk; Youn, Yeo-Chang (Frontiers in Built Environment, 2025)
Harvested wood products are a carbon pool that can be included in the national greenhouse gas inventory and are attracting attention as an important tool for reducing greenhouse gas emissions. This study evaluates the carbon reduction potential of harvested wood products by performing policy scenario analysis. It reveals that maximizing wood resource efficiency under existing policies to boost timber and sawn wood production offers the greatest reduction potential. This study found that the greenhouse gas reduction potential of the scenario with increased harvesting, in line with current government policies, is comparable to the scenario of cascading wood resource utilization without increasing harvest levels. This study provides valuable policy insights that promote national greenhouse gas reduction, while leading to a societal transformation that guarantees ecological soundness through the efficient use of domestic timber resources.